Inactivation of Gentamicin by Penicillins in Patients with Renal Failure - Ervin, F. Richard (1976)
Kinetics of gentamicin inactivation by carbenicillin and ticarcillin were studied in vitro and in 17 patients with renal failure. In vitro, the half-life of carbenicillin in human serum at 37 C is longer (19.2 ± 0.7 h) than ticarcillin (7.2 ± 0.6 h). Thus, incubation of gentamicin with equal concentrations of ticarcillin or carbenicillin results in greater inactivation of aminoglycoside activity by the latter. If concentrations of the two penicillins are held equal by repetitive addition, rates of gentamicin inactivation are the same. The serum half-life of gentamicin in patients serving as their own controls was significantly reduced by administration of either penicillin. After carbenicillin, the half-life decreased from 46 ± 8 h to 22 ± 3 h (P < 0.02). The constant for inactivation of gentamicin (k(i)) by carbenicillin was 0.02 h(−1). The results indicate that gentamicin requirements are underestimated by methods currently employed to calculate dosage for patients with renal failure who receive carbenicillin concurrently. Adjustment of gentamicin dosage in such cases by application of the k(i) for gentamicin is suggested.